CAMPUR KODE (CODE MIXING) KOMUNIKASI PADA MASYARAKAT INDIA - Ratna Sari Dewi; Dewi Nurmala (Jurnal Akrab Juara, 2018)
This objective of this study was to find out the form of code mixing, which code mixing was dominant, and what factors caused the code mixing occurred in communication of Indian community especially Tamil and Punjabi. The method used in this research was qualitative method by interview technique and observation. The sample used in this research was the purposive sampling. The number of sample was thirty people of Indian immigrants lived in Medan, especially in the Mongonsidi area of ​​Anggrung Village, Medan Polonia Subdistrict. From the resuls of the research found 54 forms of code mixing in the form of words amounted to 47 words, 5 phrases, and 2 code mixing in the form of clauses. In addition to the form of code mixing, the researcher also found several factors causing the code mixing. Based on the research that had been done, the factors causing the code mixing in communication in Indian community they were a) Background attitude of speaker, b) Potency of Opponent Speaker, and c) Familiarity. Keywords: Communication, Code Mixing, Indian Immigrants.